Protease: introduction - Salleh, Abu Bakar; Abdul Razak, Che Nyonya; Raja Abdul Rahman, Raja Noor Zaliha; Basri, Mahiran (Nova Science Publishers, 2006)
Protease can be obtained from plants, animals and microorganisms. They were grouped based on their specificities or mechanism of action. Proteases have wide industrial applications, mainly in food industry, detergent, medical and biotechnology. Many microbial proteases have been purified, characterized and commercialized. Microbial proteases are the most frequently utilized commercial enzymes with wide application in various industries such as detergent, textile, leather and food industry. Proteases comprise 60% of total enzyme sales, with detergent enzyme being the major protease user.